Spectroscopic decoding of solvent treatments in PEDOT:PSS via XPS and EPR analysis of charge transport - Akdemir, B. S.; Kol, S.; Kizildag, N.; Oral, Ahmet Yavuz (Iop Publishing Ltd, 2025)
Conductive polymer PEDOT:PSS is widely used in flexible electronics; however, the structural and electronic impacts of secondary doping remain poorly understood at the molecular level. In this study, we employ a dual-spectroscopy strategy-x-ray Photoelectron Spectroscopy (XPS) and Electron Paramagnetic Resonance (EPR)-to elucidate how ethylene glycol (EG) and dimethyl sulfoxide (DMSO) modulate the structure and charge transport properties of PEDOT:PSS films. While DMSO facilitates benzoid-to-quinoid transitions and supports polaron organization, EG promotes partial PSS removal and film morphology refinement. Spectroscopic analysis revealed a direct correlation between secondary doping-induced structural reordering and electronic structure characteristics, resulting in conductivity enhancements exceeding 400-fold relative to pristine PEDOT:PSS. By directly linking spectroscopic signatures with electrical performance, this work provides a molecular-level perspective on secondary doping effects, offering a rational basis for designing next-generation conductive polymer systems.
Keywords: PEDOT:PSS; DMSO; EG; x-ray photoelectron spectroscopy; electron paramagnetic resonance